MEMBACA PERMULAAN UNTUK ANAK USIA DINI DALAM ERA PENDIDIKAN 4.0 - Emmi Silvia Herlina (JURNAL PIONIR, 2019)
The controversy of reading for early childhood is often a debate which may or may not be given. This paper aims to answer teachers' doubts about reading activities for early childhood. Early Childhood Education is the basis for the formation of various abilities of children. Through Early Childhood Education teachers can instill strong foundations, stimulate a variety of children's potential so that later children are ready to enter the level of basic education. One of the activities that needs to be instilled early on is reading. But before reading activities are given, the teacher must first help the child to be ready to read. Early reading activities can be given to children but given in an interesting, fun and without coercion. In the era of education 4.0 which prioritizes technology, teachers are expected to be able to use technology as a learning medium to teach beginning reading.Kontraversi membaca untuk anak usia dini sering menjadi perdebatan. Boleh atau tidaknya diberikan pembelajaran membaca pada anak usia dini membuat para guru anak usia dini bingung dan takut untuk memberikan pembelajaran membaca pada peserta didik. Tulisan ini bertujuan untuk menjawab keraguan para guru mengenai kegiatan membaca untuk anak usia dini. Pendidikan Anak Usia Dini menjadi dasar pembentukan berbagai kemampuan anak. Salah satu kegiatan yang perlu ditanamkan sejak dini adalah kegiatan membaca. Pembelajaran membaca diberikan pada anak usia dini bukanlah menjadi topik perdebatan lagi namun yang harus diperhatikan adalah pembelajaran membaca diberikan dengan cara yang menarik, kreatif, menyenangkan dan tanpa paksaan. Dalam era pendidikan 4.0 yang mengedepankan teknologi, guru diharapkan mampu memanfaatkan teknologi sebagai media pembelajaran untuk mengajarkan membaca permulaan. Satu hal yang harus diperhatikan oleh guru adalah kesiapan anak dalam membaca. Guru harus membantu anak agar siap membaca dengan memberikan kegiatan yang dapat membuat anak siap membaca.